Evaluasi Pelaksanaan Program Pahasa Arab di Pondok Pesantren Al-azhar Malang - Baili; Irfan lhatif Mashur (Tadbir: Jurnal Manajemen Pendidikan Islam, 2020)
Abstrak Program evaluation is a systematic series of activities in order to find information about performance results and criteria that have been predetermined standards in order to overcome problems, or problems in program implementation. Arabic language programs hosted by the Al-Azhal Islamic boarding school are one of several programs that are still in the development stage. However, this program is able to provide motivation and interest for students to learn Arabic. In general, the implementation of the program evaluation at the boarding school of poor al-Azhar is said to be successful with good achievement indicators. Among students are able to use Arabic as an oral language in communication, and the creation of a happy Arabic learning atmosphere. the purpose of the study was to find out the process of conducting an evaluation of the Arabic Language program in Al-Azhar Islamic boarding school. In this study using a type of qualitative descriptive research, as an instrument that researchers conduct observations and interviews directly with educators, students and related parties as a source of data in this study, and as additional data, namely study documents. This study concludes that the implementation of program evaluations at the poor al-Azhar boarding school uses a discrevancy model or gap model, a Goal-Oriented Evaluation Model and a Decision-Oriented Evaluation Model. Keyword: Evaluation, program implementation, Arabic language Abstrak Evaluasi program merupakan rangkaian kegiatan yang sistematis dalam rangka mencari informasi tentang hasil kinerja dan kriteria yang menjadi standar yang telah ditetapkan sebelumnya guna mengatasi masalah-masalah, ataupun kendala dalam pelaksanaan program. program Bahasa arab dipondok pesantren Al-azhal malang merupakan salah satu dari beberapa program yang masih dalam tahap pengembangan. Meski demikian, program ini mampu memberi motivasi dan ketertarikan bagi peserta didik untuk belajar Bahasa arab.. Secara umum, pelaksanaan evaluasi program dipondok pesantren al-azhar malang dikatakan sukses dengan indikator-indikator pencapain yang baik. Diantaranya peserta didik mampu mengunakan Bahasa arab sebagai Bahasa lisan dalam berkomunikasi, dan terciptanya suasana belajar Bahasa arab yang happy. tujuan dari penelitian ialah untuk mengetahui proses pelaksaan evaluasi program Bahasa Arab di pondok pesantren Al-azhar. Dalam penelitian ini mengunakan jenis penelitian deskriftif kualitatif, sebagai instrumennya yakni peneliti melakukan observasi dan wawancara langsung kepada pendidik, peserta didik dan pihak-pihak yang terkait sebagai sumber data dalam penelitian ini, dan sebagai data tambahan yakni study dokumen. Penelitian ini menyimpulkan bahwa, pelaksanaan evaluasi program dipondok pesantren al-azhar malang mengunakan model discrevancy atau model kesenjangan, Model Evaluasi Berorientasi Tujuan dan Model Evaluasi Berorientasi Keputusan. Kata kunci: evaluasi, pelaksanaan program, Bahasa arab